Thiazolium-based crosslinked polymer and method for preparing the same

KR103031696B1Active Publication Date: 2026-10-13IND FOUND OF CHONNAM NAT UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
KR1020250098749
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2026-10-13
Estimated Expiration
2045-07-22

Smart Images

  • Figure 112025082862423-PAT00035_ABST
    Figure 112025082862423-PAT00035_ABST
Patent Text Reader

Abstract

The present invention relates to a thiazolium-based crosslinked polymer and a method for manufacturing the same. The thiazolium-based crosslinked polymer of the present invention exhibits excellent durability and reprocessability. The thiazolium-based crosslinked polymer of the present invention has excellent durability because it is crosslinked with alkyl groups between nitrogen atoms of the thiazolium ring, and it can be reprocessed as the alkyl groups dissociate and rearrange into other nitrogen atoms upon heating. Furthermore, the thiazolium-based crosslinked polymer of the present invention may additionally include functional groups in addition to the thiazolium ring, and in this case, the functional groups decompose upon UV irradiation, thereby providing recyclability. The adhesive containing the thiazolium-based crosslinked polymer of the present invention may have its adhesive performance altered when energy, such as heat or UV rays, is applied. Therefore, it may be possible to attach and detach it multiple times, or it may completely lose its adhesive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a thiazolium-based crosslinked polymer and a method for manufacturing the same, wherein the thiazolium-based crosslinked polymer of the present invention has excellent durability and reprocessability. Background Technology

[0002] Thermosetting resins chemically crosslink at high temperatures to form a three-dimensional network structure, exhibiting properties such as excellent thermal stability, mechanical strength, chemical resistance, and dimensional stability. Due to these characteristics, thermosetting resins have been used in various industries requiring high performance, including structural materials, electrical and electronic materials, and the automotive industry. However, thermosetting resins have the disadvantage that once curing is complete, they do not melt or soften even when reheated. Consequently, there are no suitable methods for recycling or disposal, making them a major cause of plastic waste. Furthermore, once thermosetting resins and molded products adhere to other products, they are difficult to separate or remove, and they are also difficult to repair if deformation occurs due to physical damage.

[0003] One method to overcome the disadvantages of the aforementioned thermosetting resins is to impart covalent adaptable networks (CANs) to the resin. A covalent adaptable network (CAN) refers to a reversible covalent bond system in which bonds are broken or reprocessed in response to external stimuli, such as heat, light, pH, or redox conditions, while maintaining the inherent strength and stability of existing covalent bonds. This combines the mechanical durability of thermosetting resins with some of the processability characteristics of thermoplastic resins through covalent bond rearrangement or reprocessing, and can exhibit useful and reversible properties such as malleability, self-healing, or shape-memory behavior. Research and development are underway regarding various mechanisms, such as associative, metathesis, and dissociative, as CAN mechanisms. For example, in bonding mechanisms such as ester exchange, amino group exchange, and silyl ether exchange, existing bonds are cleaved after new bonds are formed, thereby allowing only the bond positions to shift fluidly while maintaining crosslinking density. Vitrimer polymers are a representative example. In metathesis mechanisms, the network is rearranged as structurally similar functional groups are simultaneously exchanged, such as in disulfide exchange, boronic acid ester exchange, and olefin metathesis.

[0004] The dissociation mechanism involves the reformation of the network after existing bonds are dissociated, such as through Diels-Alder reactions, imine, or urea exchange. While this entails a temporary reduction in cross-linking and strength, chain mobility improves upon the application of external stimuli, making it useful for applications such as surface coating materials or reusable adhesives that require rapid stress relief. In particular, nitrogen-containing aromatic rings with trans-N-alkylation capabilities are expected to impart dynamic behavior to thermosetting resins, as they enable reversible bonding through alkyl groups between nitrogen atoms. While there have been limited reports of applications in development using cyclic compounds such as triazolium, anilinium, and / or pyridinium in conventional studies, the development of thermosetting polymers possessing CANs that facilitate reversible bonding and dissociation over a wide temperature range while maintaining excellent physical properties is considered a highly promising field. Prior art literature

[0005] Republic of Korea Published Patent Application No. 10-2022-0028963 The problem to be solved

[0006] The objective of the present invention is to provide a thiazolium-based crosslinked polymer having reprocessability and a method for manufacturing the same. To achieve the above objective, the thiazolium-based crosslinked polymer of the present invention has excellent durability as alkyl groups are crosslinked between nitrogen atoms of the thiazolium ring, and can have reprocessability as the alkyl groups dissociate and rearrange into other nitrogen atoms when heated.

[0007] Another objective of the present invention is to provide a thiazolium-based crosslinked polymer that not only has reprocessability but also decomposes upon UV irradiation, and a method for manufacturing the same. To achieve the above objective, the thiazolium crosslinked polymer of the present invention may further include functional groups and may provide recyclability by being easy to detach or remove after use.

[0008] Another objective of the present invention is to provide an adhesive prepared from the above-described thiazolium-based crosslinked polymer. The adhesive performance of the above-described adhesive may change when energy, such as heat or ultraviolet rays, is applied. Therefore, it may be possible to attach and detach it multiple times, or it may completely lose its adhesive performance. means of solving the problem

[0009] A thiazolium-based crosslinked polymer according to one embodiment of the present invention may include repeating units of the following chemical formula 1.

[0010] [Chemical Formula 1]

[0011]

[0012] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene can be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, L2 is a chemical bond or a C1-C10 alkylene, X is a halogen atom, and Y is And, L can be a C3-C10 alkylene.

[0013] In one embodiment, R1 is hydrogen or a C1-C3 alkyl, L1 is a C2-C10 alkylene, A is a chemical bond, L2 is a chemical bond or a C1-C3 alkylene, and X may be Cl, Br, or I.

[0014] In one embodiment, the thiazolium-based crosslinked polymer may include repeating units of the following chemical formula 3.

[0015] [Chemical Formula 3]

[0016]

[0017] Y is And, L can be a C3-C10 alkylene.

[0018] In one embodiment, the thiazolium-crosslinked polymer may include repeating units of the following chemical formula 4.

[0019] [Chemical Formula 4]

[0020]

[0021] Y is And, L can be a C3-C10 alkylene.

[0022] In one embodiment, the thiazolium-based polymer may further include a repeating unit of the following chemical formula 2.

[0023] [Chemical Formula 2]

[0024]

[0025] R2 is a C1-C10 alkoxy, -O-(L 11 -O)nR 11 or -NR 21 R 22 and; R 21 and R 22 is independently hydrogen or C1-C10 alkyl; L 11 is a C1-C10 alkylene; R 11 is a C1-C10 alkyl; n can be an integer from 1 to 5.

[0026] In one embodiment, R2 may be a C1-C6 alkoxy group.

[0027] In one embodiment, the molar ratio of the repeating units of Chemical Formula 1 and Chemical Formula 2 may be 1:50 to 1:3.

[0028] In one embodiment, the thiazolium-based polymer may be such that when heated, the Y is rearranged by a nitrogen-alkyl substitution reaction (trans-N-alkylation).

[0030] In one embodiment, the heating temperature may be 100 to 200 ℃.

[0031] In one embodiment, A may be a C6-C20 arylene substituted with NO2, and L2 may be a C1-C10 alkylene, wherein the thiazolium-based polymer may have the bond between L2 and the oxygen to which L2 is bonded separated upon UV irradiation.

[0032] A thiazole monomer according to one embodiment of the present invention may include the following chemical formula 5.

[0033] [Chemical Formula 5]

[0034]

[0035] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene may be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, and L2 may be a chemical bond or a C1-C10 alkylene.

[0036] A method for manufacturing a thiazolium-based crosslinked polymer according to one embodiment of the present invention may include the following steps: a step of manufacturing a polymer by polymerizing a monomer of Formula 5 below; and a step of mixing a crosslinking agent into the polymer and heat-curing it.

[0037] [Chemical Formula 5]

[0038]

[0039] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene may be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, and L2 may be a chemical bond or a C1-C10 alkylene.

[0040] In one embodiment, the polymer may be a copolymer further comprising a monomer of the following chemical formula 6.

[0041] [Chemical Formula 6]

[0042]

[0043] R2 is a C1-C10 alkoxy, -O-(L 11 -O)nR 11 or -NR 21 R 22 and; R 21 and R 22is independently hydrogen or C1-C10 alkyl; L 11 is a C1-C10 alkylene; R 11 is a C1-C10 alkyl; n can be an integer from 1 to 5.

[0044] In one embodiment, the crosslinking agent may include a C3-C10 alkyl dihalide.

[0045] In one embodiment, the crosslinking agent may be selected from one or more of the group consisting of 1,4-dibromobutane, 1,6-dibromohexane, 1,8-dibromooctane, 1,6-dichlorohexane and 1,6-diiodohexane.

[0046] In one embodiment, the molar ratio of the crosslinking agent to Formula 5 may be 1:1 to 1:3.

[0047] An adhesive according to one embodiment of the present invention may include the thiazolium-based crosslinked polymer.

[0048] In one embodiment, the adhesive may have a change in adhesive performance when energy is applied.

[0049] In one embodiment, the energy may be heat or ultraviolet light. Effects of the invention

[0050] The thiazolium-based crosslinked polymer of the present invention can reversibly control the physical properties of the resin by temporarily dissociating the crosslinks upon heating, and can control the rate of crosslink dissociation according to temperature conditions. That is, the thiazolium-based crosslinked polymer of the present invention not only has excellent elasticity and strength, but can also have reprocessability upon heating.

[0051] The thiazolium-based crosslinked polymer of the present invention is easy to repair when physical damage occurs and has excellent shear and peel strength, so it can be used as an adhesive. The adhesive of the present invention can be attached and detached multiple times by applying heat and removing it. In addition, the adhesive performance completely disappears upon UV irradiation, making it easy to separate and remove from the product, thus providing excellent recyclability. Brief explanation of the drawing

[0052] Figure 1 illustrates the process of crosslinking of a thiazolium-based crosslinked polymer being rearranged by heat. Figure 2 illustrates the process of decomposition of a thiazolium-based cross-linked polymer by ultraviolet irradiation. Figure 3 illustrates the shear test and peel test methods. Figure 4 illustrates the process of a cross (+) shaped scratch being restored over time on the surface of a film-shaped cS1-Bu. Figure 5 illustrates the reprocessability of the cS1-Bu polymer by heating. Figure 6 illustrates the process of a cross (+) shaped scratch being restored over time on the surface of a film-shaped cS2-Bu. Figure 7 illustrates the results of measuring the tensile strength of the cS1-Bu polymer. Pristine represents the polymer immediately after the formation of crosslinks, and Recycled represents the polymer after rearrangement following heating. Figure 8 illustrates the results of measuring the tensile strength of the cS2-Bu polymer before and after ultraviolet (UV) irradiation. Figure 9 illustrates the results of repeated shear strength measurements of the cS2-Bu polymer before and after ultraviolet (UV) irradiation. Figure 10 illustrates the results of the reprocessability evaluation of two types of commercial adhesives. Specific details for implementing the invention

[0053] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0054] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.

[0055] Throughout this specification, the terms “comprising,” “having,” “containing,” or “having” any component mean that, unless specifically stated otherwise, other components are not excluded but may be included, and do not exclude elements, materials, or processes not additionally listed.

[0056] The numerical ranges used herein include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited, and all possible combinations of upper and lower limits of the numerical range defined in different forms. Unless otherwise specifically defined in this specification, values ​​outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.

[0057] Unless otherwise specifically defined in this specification, “about” may be considered to be a value within 30%, 25%, 20%, 15%, 10%, or 5% of the specified value.

[0058] Unless otherwise specifically stated in this specification, alkyl or alkylene, etc. may be considered to include a straight chain or a branched chain.

[0059] The present invention will be described in detail below. However, this is merely illustrative and the present invention is not limited to the specific embodiments described illustratively.

[0060] A thiazolium-based crosslinked polymer according to one embodiment of the present invention may include repeating units of the following chemical formula 1.

[0061] [Chemical Formula 1]

[0062]

[0063] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene can be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, L2 is a chemical bond or a C1-C10 alkylene, X is a halogen atom, and Y is And, the above L may be a C3-C10 alkylene.

[0064] The repeating unit of Formula 1 above includes a thiazolium structure, which may refer to a structure in which the nitrogen atom of the thiazole ring is converted into a positively charged cation. Cationic polymers such as thiazolium require a corresponding anion to maintain charge balance, and the repeating unit of Formula 1 of the present invention containing thiazolium can be maintained in a stable form by a halogen anion. In addition, the thiazolium-based crosslinked polymer of the present invention can form crosslinks between the nitrogen cations of thiazolium through C3 to C10 alkylene groups, which may be represented by Y in this disclosure.

[0065] In one embodiment, R1 is hydrogen or a C1-C3 alkyl, L1 is a C2-C10 alkylene, A is a chemical bond, L2 is a chemical bond or a C1-C3 alkylene, and X may be Cl, Br, or I.

[0066] In one embodiment, the thiazolium-based crosslinked polymer may include repeating units of the following chemical formula 3.

[0067] [Chemical Formula 3]

[0068]

[0069] Y is And, L can be a C3-C10 alkylene.

[0070] In one embodiment, the thiazolium-based crosslinked polymer may include repeating units of the following chemical formula 4.

[0071] [Chemical Formula 4]

[0072]

[0073] Y is And, L can be a C3-C10 alkylene.

[0074] In one embodiment, the thiazolium-based polymer may further include a repeating unit of the following chemical formula 2.

[0075] [Chemical Formula 2]

[0076]

[0077] In one embodiment, R2 may be a C1-C10 alkoxy group. For example, (-OCH3), (-OC2H5), (-OC3H7), (-OC4H9), (-OC5H 11 ), (-OC6H 13 ), (-OC7H 15 ), (-OC8H 17 ), (-OC9H 19 ) or (-OC 10 H 21 It may be ). Preferably, R2 may be a C1-C6 alkoxy group, and more preferably a C3-C6 alkoxy group, but is not limited thereto.

[0078] In one embodiment, the R2 is -O-(L 11 -O)nR 11 It can be, and in this case, L 11 is a C1-C10 alkylene; R 11 is a C1-C10 alkyl; n may be an integer from 1 to 5. Preferably L 11 can be a C1-C3 alkylene, and R 11 can be a C1-C3 alkyl, and n can be an integer from 1 to 3. For example, R2 can be -O-(C2H4-O)2-C2H5, but is not limited thereto.

[0079] In one embodiment, the R2 is -NR 21 R 22 It can be, and in this case, R 21 and R 22Each can independently be hydrogen or a C1-C10 alkyl. For example, R 21 and R 22 are respectively methyl groups or; R 21 Silver is hydrogen, R 22 It may be an isopropyl group, but is not limited thereto.

[0080] In one embodiment, the molar ratio of the repeating units of Formula 1 and Formula 2 may be 1:50 to 1:3. The number of moles of the repeating unit of Formula 2 per mole of the repeating unit of Formula 1 may be, for example, 1:3 or more, 1:4 or more, 1:5 or more, 1:6 or more, 1:8 or more, 1:10 or more, 1:15 or more, 1:20 or more, 1:25 or more, 1:30 or more, 1:35 or more, 1:50 or less, 1:45 or less, 1:40 or less, 1:38 or less, 1:33 or less, 1:27 or less, 1:12 or less, and may be a value between these. If the number of moles of the repeating unit of Formula 2 per mole of the repeating unit of Formula 1 exceeds 50 moles, durability may decrease; conversely, if it is less than 3 moles, the crosslinking density becomes excessively high, which may reduce the flexibility and processability of the polymer. Therefore, when the molar ratio of the repeating units of Formula 1 and Formula 2 or the copolymerization molar ratio satisfies the above range, the thiazolium-based crosslinked polymer of the present invention, which has excellent durability and reprocessability, can be produced.

[0081] In one embodiment, the thiazolium-based crosslinked polymer may undergo a rearrangement of Y by a nitrogen-alkyl substitution reaction (trans-N-alkylation) upon heating. The trans-N-alkylation may refer to a reaction in which an alkyl group bonded to a nitrogen atom of a thiazolium ring moves to or is substituted for a nitrogen atom of another thiazolium ring present within the same polymer or in an adjacent chain under specific conditions. When heated to a specific temperature range, the alkyl group bonded to the nitrogen of the thiazolium ring is temporarily dissociated, which appears to be because the dissociated state exists more thermodynamically stably under high temperature conditions. In such a state, the crosslinking density is temporarily reduced, making reprocessing easier; after reprocessing into the desired shape, the alkyl group re-bonds to the nitrogen of the thiazolium ring during the cooling process to room temperature, thereby restoring the crosslinking density. Consequently, in this process, the initial bond is dissociated and rearrangement occurs. The process of the thiazolium-based crosslinked polymer of the present invention being reversibly rearranged by heat is schematically illustrated in FIG. 1.

[0082] In one embodiment, the heating temperature may be 100 to 200°C. The trans-N-alkylation reaction can proceed smoothly within the above temperature range. More preferably, the heating temperature may be 100°C or higher, 120°C or higher, 140°C or higher, 200°C or lower, 180°C or lower, 160°C or lower, or a value between these. Below 100°C, the energy required for the dissociation of the nitrogen-alkyl bond may not be sufficient, and thus the reaction may proceed very slowly. Conversely, if the heating temperature exceeds 200°C, unnecessary thermal decomposition may occur, which may have an adverse effect on the physical properties of the polymer.

[0083] In one embodiment, in the above Chemical Formula 1, A may be a C6-C20 arylene substituted with NO2, and L2 may be a C1-C10 alkylene. In this case, the thiazolium-based polymer may have the bond between L2 and the oxygen bonded to L2 separated or decomposed upon UV irradiation, and the decomposition process is schematically illustrated in FIG. 2. For example, the above Chemical Formula 1 may include a nitrobenzyl group. In this case, when UV light is absorbed, the nitro group, which has strong electron-withdrawing properties, strongly attracts electrons, inducing charge separation between CH2-O bonds and breaking the bonds.

[0084] A thiazole monomer according to one embodiment of the present invention may include the following chemical formula 5.

[0085] [Chemical Formula 5]

[0086]

[0087] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene may be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, and L2 may be a chemical bond or a C1-C10 alkylene.

[0088] In one embodiment, R1 is hydrogen or a C1-C3 alkyl, L1 is a C2-C10 alkylene, A is a chemical bond, and L2 may be a chemical bond or a C1-C3 alkylene.

[0089] A method for manufacturing a thiazolium-based crosslinked polymer according to one embodiment of the present invention may include the following steps: a step of manufacturing a polymer by polymerizing a monomer of Formula 5 below; and a step of mixing a crosslinking agent into the polymer and heat-curing it.

[0090] [Chemical Formula 5]

[0091]

[0092] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene may be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, and L2 may be a chemical bond or a C1-C10 alkylene.

[0093] In one embodiment, the polymer may be a copolymer further comprising a monomer of the following chemical formula 6.

[0094] [Chemical Formula 6]

[0095]

[0096] R2 is a C1-C10 alkoxy, -O-(L 11 -O)nR 11 or -NR 21 R 22 and; R 21 and R 22 is independently hydrogen or C1-C10 alkyl; L 11 is a C1-C10 alkylene; R 11 is a C1-C10 alkyl; n can be an integer from 1 to 5.

[0097] In one embodiment, the step of preparing the polymer may further include an initiator. Initiators that may be particularly suitable for the polymerization of the thiazolium crosslinked polymer of the present invention may include, for example, one or more selected from azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), lauroyl peroxide (LPO), or 1,1'-azobis(cyclohexanecarbonitrile) (ACHN), but are not particularly limited as long as they are commonly used in radical polymerization. Depending on the type of initiator, polymerization may be initiated by thermal initiation, photoinitiation, or redox. When using a thermal initiator such as AIBN, the polymerization temperature may be carried out at 50 to 130 °C.

[0098] In one embodiment, the step of preparing the polymer may further include a solvent. The solvent is not particularly limited as long as it has excellent solubility for organic materials during polymerization and is chemically stable so as not to affect the reactants, but examples include dimethylformamide, dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, etc.

[0099] In one embodiment, the crosslinking agent may comprise a C3-C10 alkyl dihalide. In one embodiment, the C3-C10 alkyl dihalide may be selected from one or more of the group consisting of 1,4-dibromobutane, 1,6-dibromohexane, 1,8-dibromooctane, 1,6-dichlorohexane, and 1,6-diiodohexane. More preferably, the crosslinking agent may be 1,6-dibromohexane.

[0100] In one embodiment, the molar ratio of the crosslinking agent to Formula 5 may be 1:1 to 1:3. When the molar ratio of the crosslinking agent to Formula 5 is within the above range, the reaction between the halogen atom of the crosslinking agent and the nitrogen atom of the thiazolium ring contained in Formula 5 can occur in a balanced manner. If the molar ratio falls outside the above range, one type of reaction may be insufficient, leaving an excess of reaction, which may cause unwanted side reactions or have an adverse effect on physical properties. Therefore, it may be desirable to avoid unnecessary over-feeding of raw materials and to maintain the stoichiometric balance of the reaction.

[0101] In one embodiment, the thermal curing step may further include a process of dissolving the polymer and the crosslinking agent in a solvent to disperse them uniformly. The solvent may include, but is not limited to, dichloromethane, tetrahydrofuran, acetone, etc. Additionally, the thermal curing may be performed in a temperature range of 100 to 200°C. When the thermal curing is performed at the above temperature, sufficient thermal curing can be achieved without thermal decomposition.

[0102] The thiazolium-based crosslinked polymer of the present invention possesses reprocessability and thermosetting properties. This implies that, in addition to having excellent physical properties, it may exhibit malleability, self-healing, or shape-memory behavior under specific conditions. Therefore, the thiazolium-based crosslinked polymer of the present invention can be very usefully employed in various industrial fields. For example, it can be utilized as a protective film or insulating material for electronic devices requiring reprocessability and crack recovery, as a shape-memory material subjected to repeated thermal deformation and stress conditions, or as a composite material capable of repair and recycling. Furthermore, it may be suitable for applications such as functional coating materials requiring rework, self-healing adhesives, or wear-resistant surface treatment materials. Additionally, it can be extended to flexible electrode supports for wearable electronic devices, intelligent films for biosensors, or stimulus-responsive medical polymer materials.

[0103] An adhesive according to one embodiment of the present invention may include the thiazolium-based crosslinked polymer. In one embodiment, the adhesive may have a change in adhesive performance when energy is applied. In one embodiment, the energy may be heat or ultraviolet light. Specifically, the adhesive comprising the thiazolium-based crosslinked polymer of the present invention can recover its initial adhesive performance by applying heat after detaching it by applying physical force while it is bonded. Additionally, the adhesive performance may be lost when chemical bonds are irreversibly decomposed upon ultraviolet irradiation. In this case, it can be easily removed by ultraviolet irradiation, and this may be easy to recycle.

[0104] The above-described embodiment will be explained in more detail below through examples. However, the following examples are for illustrative purposes only and do not limit the scope of the claims.

[0105] [Evaluation Method]

[0106] 1. NMR(Nuclear Magnetic Resonance)

[0107] The polymer monomer ratio, etc., were measured using Bruker Ascend 400 MHz NMR from Bruker.

[0108] 2. GPC(Gel Permeation Chromatography)

[0109] The weight-average molecular weight of the polymer was measured using a Shimadzu Prominence LC-20A instrument equipped with a differential refractive index detector (RID-20A) and an automatic sample injector (SIL-20A). A Phenogel column from Phenomenex (300 mm x 7.5 mm, 5 μm particle diameter, 100 Å pore size) was used and calibrated using a polystyrene standard. The sample concentration was 5 mg / mL, the flow rate was 1 mL / min, and HPLC-grade THF was used as the solvent.

[0110] 3. Tensile strength

[0111] Measurements were taken using a universal testing machine (UTM) from A&D Company (model name: MCT-2150). A specimen (2.5 mm x 7 mm x 0.15 mm) was attached between two glass slides using a super-strong adhesive. The specimen was tensile at a speed of 10 mm per minute until fracture, and a stress-strain curve was derived.

[0112] 4. Shear strength

[0113] Measurements were taken using a universal testing machine (UTM) from A&D Company (model name: MCT-2150). A specimen (width x length x thickness: 2.5 mm x 7 mm x 0.15 mm) was attached between two glass slides. The specimen was extended at a speed of 10 mm per minute until it separated from the glass slides, and a stress-strain curve was derived. The average value of the shear strength was recorded after five repeated measurements. The shear strength measurement test method is illustrated on the left side of Figure 3.

[0114] 5. Peel strength

[0115] Measurements were taken using a universal testing machine (UTM) from A&D Company (model name: MCT-2150). A specimen (width x length x thickness: 2.5 mm x 7 mm x 0.15 mm) was attached between two glass slides. Additionally, a polypropylene film was adhered to the glass, and the film was extended at a speed of 10 mm per minute at angles of 0° and 180°, respectively, until the specimen separated from the glass slide, and a load-displacement curve was derived. The peel strength was measured five times, and the average value was recorded. The peel strength measurement test method is illustrated on the right side of Fig. 3.

[0116] [Preparation Example 1] Method for preparing functional monomer S1

[0117] 5-(2-hydroxyethyl)-4-methyldiazole (1000 mg, 6.98 mmol, 1 equivalent), triethylamine (1060 mg, 10.47 mmol, 1.5 equivalents), and 20 mL of dry dichloromethane were mixed, and the mixture was cooled to 0 °C. Subsequently, acryloyl chloride (758.41 mg, 8.38 mmol, 1.2 equivalents) was added dropwise in small amounts, and the mixture was stirred at room temperature for 12 hours. After the reaction was complete, 20 mL of dichloromethane was added to the reaction mixture to dilute it, and it was washed with 30 mL of sodium bicarbonate aqueous solution and 30 mL of distilled water. The washed reaction mixture was collected, anhydrous sodium sulfate (Na2SO4) was added, dried, filtered, and concentrated under reduced pressure. The above reaction mixture was purified by flash column chromatography using a mixed solvent with a weight ratio of n-hexane to ethyl acetate of 7:3, and concentrated under reduced pressure. By the above method, the functional monomer S1 of the following chemical formula 7 was obtained.

[0118] [Chemical Formula 7] Functional monomer S1

[0119]

[0120] [Preparation Example 2] Method for preparing functional monomer S2

[0121] Compound 1 of Reaction Scheme 1 below (550 mg, 2.44 mmol, 1.0 equivalent), 5-(2-hydroxyethyl)-4-methylthiazole (349.84 mg, 2.44 mmol, 1.0 equivalent), 4-dimethylaminopyridine (59.69 mg, 0.49 mmol, 0.2 equivalent), and 50 mL of dry dichloromethane were mixed. 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (561.95 mg, 2.93 mmol, 1.2 equivalent) was added to the mixture and stirred at room temperature for 12 hours. The reaction mixture was filtered and concentrated under reduced pressure, then purified by flash column chromatography using a mixed solvent with a weight ratio of n-hexane to ethyl acetate of 5:5, and concentrated under reduced pressure. Compound 2 of the following reaction scheme 1 was obtained by the above method.

[0122] Compound 2 (120 mg, 0.34 mmol, 1.0 equivalent) prepared above was dissolved in 2.5 mL of co-solvent (dichloromethane:ethanol:acetic acid = 35:5:1) at a temperature of 0 °C under a nitrogen atmosphere. Subsequently, NaBH4 (25.91 mg, 0.69 mmol, 2.0 equivalent) was added to the solution, the temperature was maintained at 0 °C, and the mixture was stirred for 2 hours. Then, 0.25 mL of hydrochloric acid was added to stop the reaction. The reaction mixture was diluted with 10 mL of ethyl acetate and washed with 15 mL of water and 12 mL of brine. Sodium sulfate (Na2SO) was added to the reaction mixture, dried, filtered, and concentrated under reduced pressure. Compound 3 of Reaction Scheme 1 below was obtained by the above method.

[0123] Compound 3 (590 mg, 1.67 mmol, 1.0 equivalent) prepared above, triethylamine (389.93 mg, 2.51 mmol, 1.5 equivalent), and 5 mL of dichloromethane were mixed under a nitrogen atmosphere. After cooling the mixture to 0 °C, acryloyl chloride (181.86 mg, 2.01 mmol, 1.2 equivalent) was added dropwise in small amounts, and the mixture was stirred at room temperature for 12 hours. After the reaction was completed, 12 mL of dichloromethane was added to the reaction mixture to dilute it, and it was washed with 20 mL of sodium bicarbonate aqueous solution and 20 mL of distilled water. The washed reaction mixture was collected, anhydrous sodium sulfate (Na2SO4) was added, dried, filtered, and concentrated under reduced pressure. The above reaction mixture was purified by flash column chromatography using a mixed solvent with a weight ratio of n-hexane to ethyl acetate of 5:5, and concentrated under reduced pressure. By the above method, the functional monomer S2 of the following chemical formula 8 was obtained.

[0124] [Chemical Formula 8] Functional monomer S2

[0125]

[0126] [Reaction Equation 1]

[0127]

[0128] In the above reaction equation 1, R is am.

[0129] [Example 1] Method for preparing thiazolium-based polymer cS1-Bu

[0130] S1 (50 mg, 0.25 mmol, 1.0 equivalent) prepared in Preparation Example 1, butyl acrylate (292.40 mg, 2.28 mmol, 9.0 equivalent), azobisisobutyronitrile (4.16 mg, 0.03 mmol, 0.1 equivalent), and 0.3 mL of dimethylformamide were mixed under a nitrogen atmosphere. After degassing with nitrogen gas for 20 minutes, the mixture was stirred at 85 °C for 2 hours. 1.5 mL of diethyl ether was added to the reaction mixture, precipitated, and dried under reduced pressure. The mixture was redissolved in 5 mL of dichloromethane, and 1.5 mL of diethyl ether was added to re-precipitate to obtain a wax-like polymer pS1-Bu. As a result of NMR measurement of the above pS1-Bu polymer, the ratio of repeating units by S1 monomer to repeating units by butyl acrylate monomer was 1:7, and as a result of GPC measurement, the molecular weight was approximately 70,000 g / mol.

[0131] 120 mg of the above-prepared pS1-Bu polymer and 0.05 mg of 1,6-dibromohexane were dissolved in 1.5 mL of dichloromethane. The solution was poured between Teflon sheets and cured in an oven at 150°C for 3 days to obtain a film-type thiazolium-based polymer cS1-Bu.

[0132] [Example 2] Method for preparing thiazolium-based polymer cS2-Bu

[0133] S2 (20 mg, 0.05 mmol, 1.0 equivalent) prepared in Preparation Example 2, butyl acrylate (624.43 mg, 4.87 mmol, 99.0 equivalent), azobisisobutyronitrile (8.08 mg, 0.05 mmol, 1.0 equivalent), and 0.3 mL of dimethylformamide were mixed under a nitrogen atmosphere. After degassing with nitrogen gas for 20 minutes, the mixture was stirred at 85 °C for 2 hours. 2.0 mL of diethyl ether was added to the reaction mixture, precipitated, and dried under reduced pressure. The mixture was redissolved in 10 mL of methanol, and 2.0 mL of diethyl ether was added to re-precipitate it to obtain a wax-like polymer pS2-Bu. As a result of NMR measurement of the above pS2-Bu polymer, the ratio of repeating units by S2 monomer to repeating units by butyl acrylate monomer was 1:36, and as a result of GPC measurement, the molecular weight was approximately 84,000 g / mol.

[0134] 100 mg of the above-prepared pS2-Bu polymer and 0.009 mg of 1,6-dibromohexane were dissolved in 1.2 mL of dichloromethane. The solution was poured between Teflon sheets and cured in an oven at 150°C for 3 days to obtain a film-type thiazolium-based polymer cS2-Bu.

[0135] [Evaluation Example 1] Evaluation of Reworkability and Tensile Strength

[0136] Cross-shaped (+) scratches were formed on the above-prepared cS1-Bu (Fig. 4) and cS2-Bu (Fig. 6), films with a thickness of 0.4 mm. When heated to 150 ℃, the scratches gradually healed and were completely restored within 1 hour. As can be seen in Fig. 5, it was observed that the shape and physical properties of the torn cS1-Bu film were completely restored after heating at a temperature of 150 ℃ for 12 hours.

[0137] As shown in Fig. 7, the tensile stress-strain curve of the cS1-Bu film was measured, and the Young's modulus was measured to be 0.05 ± 0.01 MPa and the elongation at break was approximately 880%. Therefore, it was found that the cS1-Bu polymer or film is very flexible and has excellent elasticity. When the tensile stress-strain curve was re-measured after the film was torn by applying physical force and then heated at 150°C for 12 hours, it was found that the elastic modulus was fully recovered.

[0138] [Evaluation Example 2] Evaluation of Shear Strength and Peeling Strength

[0139] To evaluate the adhesive properties of cS1-Bu, shear strength and peel strength were measured using the evaluation method described above. The shear and peel strengths of pS1-Bu, a linear polymer, were found to be up to 0.02 MPa and 2.1 N / cm, respectively. There was almost no change in strength when the crosslinking agent was simply mixed without heating, or when heating was performed without the crosslinking agent, as thiazolium crosslinking was not formed. On the other hand, the shear and peel strengths of cS1-Bu were found to be up to 0.2 MPa and 6.9 N / cm, respectively. Furthermore, it was observed that the shear strength and peel strength decreased significantly when the specimens were separated by applying physical force after being bonded by heating and then rejoined at room temperature. It was found that when the same specimen was reheated at 150°C for 0.5 hours, the shear strength and peel strength were fully recovered, and these reversible characteristics were consistently maintained during additional separation and re-adhesion cycles. The results for the shear strength and peel strength (180° peel strength) described above were measured using the evaluation method described above and are shown in Table 1. Figure 10 shows the same experiment conducted on commercial polycyanoacrylate and double-sided tape, where it can be seen that when separated by applying physical force after the first attachment, the shear strength and peel strength are not recovered at all even when heat is applied.

[0140] shear strength(MPa) 180° peel strength(N / cm) 1st heating 0.20 6.1 Rejoined 0.05 2.1 2nd heating 0.18 6.9 Rejoined 0.02 2.0 3rd heating 0.17 5.9 Rejoined 0.02 1.9 4th heating 0.18 6.2

[0141] [Evaluation Example 3] Comparative evaluation of cS2-Bu before and after UV irradiation

[0142] Figure 2 illustrates the cleavage sites of the cS2-Bu polymer upon UV irradiation. Figure 8 illustrates a comparative stress-strain curve of the cS2-Bu polymer before and after UV irradiation. The elastic modulus of cS2-Bu was measured to be 0.13 MPa, which is higher than that of cS1-Bu. This indicates that strength can be improved when nitrobenzyl groups are present in the monomer, even though the number of thiazolium crosslinks decreases. Significant changes in mechanical properties were observed, such as a significant decrease in the elastic modulus of cS2-Bu to less than 0.01 MPa when exposed to UV light below 365 nm. On the other hand, cS1-Bu exhibited a constant elastic modulus regardless of UV irradiation.

[0143] As shown in Figure 9, shear strength was measured to investigate the adhesive properties of cS2-Bu. The shear strength before UV irradiation was approximately 0.2 MPa, which was similar to that of cS1-Bu. Similar to cS1-Bu, specimens re-bonded without heat treatment did not recover their initial adhesive strength; however, heating fully restored it, demonstrating that it could be reused after four additional separation-heating cycles. In contrast, the shear strength decreased sharply after UV irradiation and did not recover even with repeated separation-heating cycles. Therefore, it was found that while cS2-Bu exhibits excellent adhesive performance and reprocessability, it can be easily detached within 10 seconds after UV irradiation. This overcomes the disadvantage of conventional thermosetting materials, which are difficult to detach; it possesses sufficient strength when used with polymer materials but is easy to remove after use. Consequently, it can be easily separated after use as an adhesive and can also be separated from other attached materials during disposal.

[0144] From Evaluation Examples 1 to 3 above, the thiazolium-based polymer of the present invention has excellent strength and possesses recyclability by retaining reprocessability by heat. Furthermore, additional functionalization of the monomer creates photodegradable thiazolium crosslinks, which not only provides recyclability but also induces the release of crosslinks by light, allowing for conversion to a non-adhesive state. Thus, the present invention presents a novel design of a covalent adaptive network (CAN) containing thiazolium as a core unit, and can be utilized as a reversible and degradable flexible material suitable for coating materials, adhesives, and bio-related applications.

[0145] As described above, the present invention has been explained by specific details and limited embodiments; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.

[0146] Accordingly, the present invention is not limited to the embodiments described above, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to be within the scope of the present invention.

Claims

Claim 1 A thiazolium-based crosslinked polymer comprising repeating units of the following chemical formula 1. [Chemical Formula 1] R1 is hydrogen or a C1-C10 alkyl, L1 is a C2-C10 alkylene, the CH2 of the alkylene can be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, L2 is a chemical bond or a C1-C10 alkylene, X is a halogen atom, and Y is And, L is a C3-C10 alkylene. Claim 2 A thiazolium-based crosslinked polymer according to claim 1, wherein R1 is hydrogen or C1-C3 alkyl, L1 is C2-C10 alkylene, A is a chemical bond, L2 is a chemical bond or C1-C3 alkylene, and X is Cl, Br, or I. Claim 3 The thiazolium-based crosslinked polymer of claim 1, comprising a repeating unit of the following chemical formula 3. [Chemical Formula 3] Y is And, L is a C3-C10 alkylene. Claim 4 The thiazolium-based crosslinked polymer of claim 1, comprising a repeating unit of the following chemical formula 4. [Chemical Formula 4] Y is And, L is a C3-C10 alkylene. Claim 5 The thiazolium-based crosslinked polymer of claim 1, wherein the thiazolium-based crosslinked polymer further comprises a repeating unit of the following Chemical Formula 2. [Chemical Formula 2] R2 is a C1-C10 alkoxy, -O-(L 11 -O)nR 11 or -NR 21 R 22 Igo;R 21 and R 22 are each independently hydrogen or C1-C10 alkyl; L 11 is a C1-C10 alkylene and R 11 is a C1-C10 alkyl; n is an integer from 1 to 5. Claim 6 In claim 5, the above R2 is a thiazolium-based crosslinked polymer in which the R2 is a C1-C6 alkoxy group. Claim 7 A thiazolium-based crosslinked polymer according to claim 5, wherein the molar ratio of the repeating units of Chemical Formula 1 and Chemical Formula 2 is 1:50 to 1:

3. Claim 8 The thiazolium-based crosslinked polymer according to claim 1, wherein the thiazolium-based crosslinked polymer is one in which the Y is rearranged by a nitrogen-alkyl substitution reaction (trans-N-alkylation) upon heating. Claim 9 A thiazolium-based crosslinked polymer according to claim 8, wherein the heating temperature is 100 to 200 ℃. Claim 10 A thiazolium-based crosslinked polymer according to claim 1, wherein A is a C6-C20 arylene substituted with NO2 and L2 is a C1-C10 alkylene. Claim 11 In claim 10, the thiazolium-based crosslinked polymer is a thiazolium-based crosslinked polymer in which the bond between L2 and the oxygen to which L2 is bonded is separated upon ultraviolet irradiation. Claim 12 A thiazole monomer comprising the following chemical formula 5 [Chemical Formula 5] R1 is hydrogen or C1-C10 alkyl, L1 is C2-C10 alkylene, CH2 of the alkylene can be replaced with -O- or -C(=O)-, A is C6-C20 arylene substituted with NO2, and L2 is C1-C10 alkylene. Claim 13 A method for preparing a thiazolium-based crosslinked polymer, comprising: a step of preparing a polymer by polymerizing a monomer of the following chemical formula 5; and a step of mixing a crosslinking agent into the polymer and heat-curing it. [Chemical Formula 5] R1 is hydrogen or C1-C10 alkyl, L1 is C2-C10 alkylene, CH2 of the alkylene can be replaced with -O- or -C(=O)-, A is a chemical bond or a C6-C20 arylene substituted with NO2, and L2 is a chemical bond or a C1-C10 alkylene. Claim 14 A method for preparing a thiazolium-based crosslinked polymer according to claim 13, wherein the polymer is a copolymer further comprising a monomer of the following chemical formula 6. [Chemical Formula 6] R2 is a C1-C10 alkoxy, -O-(L 11 -O)nR 11 or -NR 21 R 22 Igo;R 21 and R 22 are each independently hydrogen or C1-C10 alkyl; L 11 is a C1-C10 alkylene and R 11 is a C1-C10 alkyl; n is an integer from 1 to 5. Claim 15 A method for manufacturing a thiazolium-based crosslinked polymer according to claim 13, wherein the crosslinking agent comprises a C3-C10 alkyl dihalide. Claim 16 A method for manufacturing a thiazolium-based crosslinked polymer, wherein the crosslinking agent in claim 13 is selected from one or more of the group consisting of 1,4-dibromobutane, 1,6-dibromohexane, 1,8-dibromooctane, 1,6-dichlorohexane and 1,6-diiodohexane. Claim 17 A method for preparing a thiazolium-based crosslinked polymer according to claim 13, wherein the molar ratio of the crosslinking agent to Formula 5 is 1:1 to 1:

3. Claim 18 An adhesive comprising a thiazolium-based crosslinked polymer selected from any one of claims 1 to 11. Claim 19 In paragraph 18, an adhesive whose adhesive performance changes when energy is applied. Claim 20 In paragraph 19, the adhesive, wherein the energy is heat or ultraviolet light.

Citation Information

Patent Citations

  • Preparation method of self-driven propeller-shaped bimetallic coordination polymer functional material

    CN115414918A

  • Photopolymerizable composition containing thioether

    JP1995320299A

  • Adhesion adjuvant, adhesive treatment solution for a rubber composition-fiber composite, and rubber composition-fiber composite

    JP2014152271A

  • Heat-peelable adhesive composition and adhesive sheet

    JP2023181766A

  • Curable composition containing benzothiazolium salt compound

    JP3353323B2